JURIDICAL ANALYSIS OF JOTOSANUR VILLAGE REGULATIONS IN THE PREVENTION OF CORRUPTION CRIMES - M. Yanto; Ja'far Shodiq; Chusnul Khitam (ASIAN PUBLISHER, 2025)
Village government has a strategic role in village financial management based on Law Number 6 of 2014 concerning Villages. However, the management of village funds that is not transparent and accountable has the potential to give rise to corruption crimes. The Jotosanur Village Regulation is present as a preventive effort to prevent corrupt practices through good governance arrangements. This research uses a normative juridical approach by analyzing laws and regulations, literature, and related documents, such as Law Number 6 of 2014, Regulation of the Minister of Home Affairs Number 113 of 2014. The Jotosanur Village Regulation regulates the management of village funds, budget transparency, and supervision by the Village Consultative Body (BPD) and the community. This provision is in line with the principles of good governance, namely transparency, accountability, and community participation. However, implementation faces challenges such as low capacity of village officials and lack of community participation. Internal and external oversight mechanisms, as well as anti-corruption education, are important factors in supporting the effectiveness of these regulations. The Jotosanur Village Regulation has a strong legal foundation and has the potential to be effective in preventing corruption through strengthening village governance. However, its effectiveness depends on increasing the capacity of village officials, community participation, and synergy with relevant institutions.